Situation Awareness Scheme Based on PUE Detecting for Cognitive Radio - Fangwei Li; Dejun Feng; Jiang Zhu (Dianxin kexue)
To timely and accurately grasp the attack situation over a wide range when a malicious user emulates the primary user and attacks the channel, and to display correctly spectrum situation, a situation awareness scheme for the interference situation of malicious users was proposed. Decision-makers can know well the attack situation over a wide range, by detecting the primary user emulation attacker's energy and location to build the interference situation, and drew the interference into a situation map. The proposed approach can separate the energy and position of the primary users and malicious users, so as to fully exploit the potential of spectrum holes to improve the accuracy of the spectrum map, and improve safety and system capacity of the channels.